Screening Greenland in Borgen - Power & Glory : The on- and off-screen contestedness of Arctic landscapes and locations - Grønlund, Anders; Risum Waade, Anne Marit (Critical Studies in Television: The International Journal of Television Studies, 2024)
This article shows how the Arctic landscapes in the Danish political drama series Borgen: Power & Glory demonstrate Greenland as a contested land in distinct ways: culturally due to the postcolonial tension between Denmark and Greenland; politically due to the conflicted interests from Denmark and other nations for the country’s natural resources; environmentally due to the looming transformation of the Arctic landscapes due to global warming, and commercially due to increasing interest in screen production from Greenlandic tourism actors. Furthermore, we contribute to the location study method approach by focusing on location management and the contestedness of the industry itself.